What is the Black Lives Matter movement? - Nichols, Hedreich; Wing, Kelisa (Racial justice in America., 2021)
Explores the history and work of the Black Lives Matter movement, and highlights ways people can get involved with the Black Lives Matter movement. Includes color and black-and-white photographs, an activity, a glossary, and additional resources.